Spectral domain approach applied to the rigorous determination of the microwave field in planar structures with asymmetric electrodes distribution - Crivellaro de Menezes, Joao Paulo; Silva Lemes, Andryos da; Barbosa Oliveira, Jose Edimar; Kitano, Claudio [UNESP] (Wiley-Blackwell, 2020)
Among several methods used for designing microstrip-like microwave and millimetre-wave waveguides, we have the spectral domain approach (SDA), which allows determining parameters such as effective permittivity and characteristic impedance of multi-electrode and multi-layer structures. SDA is also important for designing integrated optical phase modulators, especially for computing the electromagnetic field distribution, which is essential for the determination of their half-wave voltage and frequency bandwidth. However, it was verified that when SDA technique is applied to the computation of the field pattern inside boxed waveguides with asymmetric electrode distribution, accurate results were not obtained. Since electrical quantities in SDA, including electromagnetic field, depend on the current distribution on the electrodes, a formulation taking into account the method of images for the correct description of these currents can solve the drawback. Simulations show that using asymmetric electrodes in lithium-niobate-based coplanar strip (CPS) modulators, although not very usual, can provide an extra degree of freedom to their designs. We show that is possible to reduce the effective permittivity, obtain characteristic impedances nearer 50 omega, and double the peak amplitude for the pi-mode electric field compared to that obtained for odd mode on symmetric CPS. This can improve the performance of travelling-wave electro-optic modulators.